Analisis Profesi, Persyaratan Kerja dan hasil kerja akuntan terhadap Mahasiswa di Kota Batam - Jenniver Jenniver; Mortigor Afrizal Purba (Politeknik Ganesha Medan, 2022)
The purpose of this research is to examine accounting students in Batam City who have a career in public accounting which measures the accounting profession, job requirements and work results of accountants. The extent to which the accounting profession, accountants work requirements and accountants' work results affect the career choices of students in the public accounting sector. This study used a sample of 302 undergraduate students from various universities in Batam City. The questionnaire consists of 20 question items which use a Likert scale ranging from strongly disagree to strongly agree. The distribution of the questionnaire was completed in mid-October 2021. The data used descriptive statistics that had been collected were entered and analyzed using the SPSS version 26 program. Public accountants have a working profession so that researchers found that accounting was rated higher by respondents in relation to the work of accountants as a profession. boring, routine and monotonous. Then, in connection with the choice of a career as a public accountant from Batam City students, it shows that the choice of a career as a public accountant is more dominant than other accountants such as corporate accountants. Thus, corporate policy makers should help to make the corporate accounting sector more attractive and educate students about the importance of being a financial steward in a company. Despite the limitations of the study it would still be useful for policy makers to create new or new ideas and modify their strategies with respect to the problems identified